Risk factors for prostate cancer, and motivational and hindering aspects in conducting preventive practices - Gontijo Gomes, Cássia Regina; Resende Izidoro, Lívia Cristina; Ferreira da Mata, Luciana Regina (Investigación y Educación en Enfermería, 2015)
Objective. Identify risk factors for Prostate Cancer (PC), preventive practices, and hindering and motivating factors for disease prevention among workers of a public university. Methodology. A descriptive study, conducted with 92 workers who answered a self-administered questionnaire on the variables related to sociodemographic characteristics and clinical risk factors, sources of information about PC, practices related to prevention, and information on the hindering and motivating factors for prevention of the disease. Results. Most (95.0%) participants had one or more risk factors for PC; 68.5% underwent completion of the prostate-specific antigen (PSA) test annually at the request of the university; 50.0% of participants never performed the digital rectal examination (DRE); the main source of information was the media (64.1%); the main complicating factor for realization of the yearly preventive screening test was the lack of request for examination by their doctor; and the main motivating reason was recognition of the severity of the disease. Conclusion. Most participants had risk factors for the disease, do not perform the DRE, presented difficulties in carrying out prevention, and revealed they do not receive information about the disease from healthcare professionals, which could in turn lead to an erroneous understanding, resulting in hindering factors for practices to prevent PC. Thus, health care managers and multidisciplinary teams should engage in preventive health care for men in order to initiate preventive practices, and clarify any doubts about the disease. How to cite this article: Gomes CRG, Izidoro LCR, Mata LRF. Risk factors for prostate cancer, and motivational and hindering aspects in conducting preventive practices. Invest Educ Enferm. 2015; 33(3):